Basics of analytical chemistry and chemical equilibria a quantitative approach - Tissue, Brian M. 1961- (John Wiley & Sons Inc., 2023)
"This text will introduce you to analytical chemistry: the science of making quantitative measurements. Quantifying the individual components in a complex sample is an exercise in problem solving. An effective and efficient analyst will have expertise in sampling, sample processing, and method validation; the chemistry that can occur in a sample before and during analysis; selecting an appropriate analytical method; and proper record keeping, data analysis, and reporting of results. I do not attempt to be comprehensive in this text. Samples that require analysis are so diverse that it is not possible to describe every sample preparation protocol, separation method, and measurement technique. These details are contained in handbooks and method compilations, many of which are now accessible from online sources. This text emphasizes the fundamental chemical and physical concepts that underlie the analytical methods. With an understanding of the fundamental concepts, a scientist faced with a difficult analysis can apply the most appropriate techniques, identify when a particular problem cannot be solved with existing methods, and develop new analytical methods. The proficient analyst will also be alert to interferences and problems in analytical measurements and recognize when an answer might not be correct. I organize the discussion of the core principles of analytical chemistry into three parts: Part I: analytical concepts such as calibration and uncertainty, sample preparation, classical (wet-chemical) methods, and molecular UV/Vis spectroscopy Part II: chemical equilibria involving acids, bases, complexes, and insoluble precipitates Part III: electroanalytical methods, atomic spectrometry, molecular structure determination, and chromatographic separations"--Provided by publisher.